From Concessions to Conflict: Strategic, Economic, and Ideological Drivers of U.S. Military Action Against the Barbary States in the Mediterranean in the Eighteenth and Nineteenth Centuries - Tien, Nguyen Thi Kim; Chinh, Phan Nguyen Huy (Journal of Cultural Analysis and Social Change, 2025)
The paper analyzes the evolution of U.S. policy in addressing the Barbary pirates in the Mediterranean during the 18th–19th centuries, a major issue impacting trade, national honor, and the image of the United States in its early years of independence. The study focuses on factors leading to a shift from appeasement through disadvantageous treaties to declarations of war and the use of military force. Employing historical methods, the paper examines sources ranging from diplomatic documents and firsthand witness accounts to studies on international relations and the American economy to clarify the issues at hand. The paper explores key aspects such as the impact of slavery and trade losses caused by the pirates, the budgetary burdens of ransom and tribute payments, the role of the newly established U.S. Navy, and policy changes across presidential administrations, particularly under Thomas Jefferson, which contributed to shifts in American policy toward the Barbary States. The research findings suggest that the changes in U.S. policy were driven by economic losses, social pressures, the need for free trade, and national honor. The development of naval forces and proactive diplomacy emerged as decisive factors leading to victories in the First Barbary War (1801–1805) and the Second Barbary War (1815–1816). The research not only sheds light on a pivotal period in American history but also offers perspectives on the transition from peaceful policies to the use of force against international threats, emphasizing the importance of building naval and diplomatic strength to protect national interests in an unpredictable global context.